Security, Privacy and Trust in Cloud Systems - Nepal, Surya; Pathan, Mukaddim; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
The book compiles technologies for enhancing and provisioning security, privacy and trust in cloud systems based on Quality of Servise requirements. It is a timely contribution to a field that is gaining considerable research interest, momentum, and provides a comprehensive coverage of technologies related to cloud security, privacy and trust. In particular, the book includes - Cloud security fundamentals and related technologies to-date, with a comprehensive coverage of evolution, current landscape, and future roadmap. - A smooth organization with introductory, advanced and specialist content, i.e. from basics of security, privacy and trust in cloud systems, to advanced cartographic techniques, case studies covering both social and technological aspects, and advanced platforms. - Case studies written by professionals and/or industrial researchers. - Inclusion of a section on Cloud security and eGovernance tutorial that can be used for knowledge transfer and teaching purpose. - Identification of open research issues to help practitioners and researchers. The book is a timely topic for readers, including practicing engineers and academics, in the domains related to the engineering, science, and art of building networks and networked applications. Specifically, upon reading this book, audiences will perceive the following benefits: 1. Learn the state-of-the-art in research and development on cloud security, privacy and trust. 2. Obtain a future roadmap by learning open research issues. 3. Gather the background knowledge to tackle key problems, whose solutions will enhance the evolution of next-generation secure cloud systems.
Part I Cloud Computing Fundamentals -- Introduction to cloud computing -- Secure information sharing and data protection in the cloud -- Intra and inter-cloud security, privacy and trust -- Cloud-based eGovernance -- Part II Cloud Security -- Cloud security architecture and protocol -- Secure cloud data management service -- Security and virtualization -- Autonomic security in cloud systems -- Part III Cloud Privacy -- Cryptography and crypto-protocols for cloud systems -- Access control mechanisms -- Risk management in the cloud -- Privacy protection policies in cloud platforms and operations -- Part IV Cloud Trust -- Trust models for cloud services -- QoS-based trust model and QoS monitoring mechanism -- Cloud compliance -- Non-repudiation and reputation in the cloud -- Part V Case Studies -- Secure cloud platforms and applications -- Enterprise cloud security case study -- Open research issues in cloud security and future roadmap -- Cloud and eGovernment tutorial: Challenges, solutions and experiences.
Keywords: Engineering; Data protection; Data encryption (Computer science).; Telecommunication; Engineering; Communications Engineering, Networks; Systems and Data Security; Data Encryption